2020
DOI: 10.1167/iovs.61.12.21
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Loss of Yap1 in Mice Causes Progressive Cataracts

Abstract: Purpose Yap1 encodes an evolutionarily conserved transcriptional coactivator and functions as a down-stream effector of the Hippo signaling pathway that controls tissue size and cell growth. Yap1 contributes to lens epithelial development. However, the effect of Yap1 haplodeficiency on the lens epithelium and its role in the development of cataracts has not been reported. The aim of the current study is to investigate Yap1 function and its regulatory mechanisms in lens e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…293 In addition to retinal-related diseases, the heterozygous inactivation of YAP1, which decreases the expression of YAP1 protein in lens epithelia, results in cataracts with lens epithelial cell defects. 294 Moreover, NF2 deficiency in the lens epithelium in mice could lead to a cataract phenotype. 64 The Hippo pathway in cardiac diseases.…”
Section: Dysregulation Of the Hippo Pathway And Human Diseasesmentioning
confidence: 99%
“…293 In addition to retinal-related diseases, the heterozygous inactivation of YAP1, which decreases the expression of YAP1 protein in lens epithelia, results in cataracts with lens epithelial cell defects. 294 Moreover, NF2 deficiency in the lens epithelium in mice could lead to a cataract phenotype. 64 The Hippo pathway in cardiac diseases.…”
Section: Dysregulation Of the Hippo Pathway And Human Diseasesmentioning
confidence: 99%
“…33 In addition, YAP is necessary to preserve the normal size of the lens. 34 The lens epithelium was significantly reduced in mice with conditionally deleted YAP. 33 Loss of YAP inhibits proliferation, promotes abnormal differentiation and senescence of LECs, and eventually leads to an abnormal lens structure and nuclear cataract formation.…”
Section: Dumentioning
confidence: 99%
“…22 Recent studies have demonstrated that, in mice, one allelic deletion of Yap1 dramatically lowered LEC cell density, disrupted local cell adhesion and caused cataracts. 34,35 Liu et al…”
Section: Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Gain or loss of YAP function modulates the expression of genes that regulate cell proliferation and survival (diap1, bantam, cyclin E, and E2F1), the Hippo pathway (Kibra, Crb, and Fj), and cell-cell interaction (E-Cadherin, Serrate, Wingless, and Vein) (Pan 2010). The role of YAP in the regulation of ocular tissue development and function has been extensively studied (Kastan et al 2022;Lu et al 2020). Indeed, YAP has been shown to be expressed in the RPE and the ciliary margin of the optic cup as well as corneal epithelial and lens epithelial cells, iris, and retina where it localized in the inner nuclear layer (Hamon et al 2019(Hamon et al , 2017.…”
Section: Yap Signaling In Retinal Neurogenesis and Gliogenesismentioning
confidence: 99%